Rancang Bangun Sistem Informasi Penjualan “Pasar Kita” Di Pasar Tradisional Dringu Berbasis Web - Yahya Yulianto; Dyah Ariyanti; Ary Analisa Rahma (Fakultas Teknik, 2023)
As technology advances and people's needs for shopping, considering that currently shopping can be accessed through applications. The Probolinggo District Office of Industry and Trade facilitates buying and selling without entering the market, shopping online through the WhattsApp and Instagram applications with the